2023
DOI: 10.1021/acsanm.3c00780
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle Delivery to Solid Tumors by Macrophage Depletion, Hypoxia Inhibition, and Collagen Degradation

Abstract: The delivery of nanomaterials (NMs) to solid tumors remains a heavily researched topic, and while significant efforts have been aimed at optimizing NM design for active tumor targeting, it has become clear that the aberrant and heterogeneous nature of the tumor microenvironment (TME) serves as a physical barrier to NM uptake by tumor cells. In our previous work, we show that NM delivery efficacy is dependent on NM size and is linked to various TME parameters, with the levels of tumorassociated macrophages (TAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Although the existing AuNP-bio interaction literature is largely focused on the direct interactions between AuNPs and cells (such as uptake, cytotoxicity, and gene expression), it has also been observed that AuNPs can influence cell behavior indirectly by modifying the local microenvironment. Recent work has shown that AuNPs can disrupt cross talk between cells and alter the mechanical and chemical properties of the extracellular matrix (ECM). This disruption can extend to cellular behaviors such as chemotaxis, the directed migration of cells in response to a chemical gradient. Chemotaxis is responsible for infection and would healing in humans and can be greatly affected by changes in the ECM. Dysfunctions in cellular chemotaxis have been implicated in a variety of health problems such as chronic obstructive pulmonary disease, cystic fibrosis, infertility, and cancer metastasis. , …”
mentioning
confidence: 99%
“…Although the existing AuNP-bio interaction literature is largely focused on the direct interactions between AuNPs and cells (such as uptake, cytotoxicity, and gene expression), it has also been observed that AuNPs can influence cell behavior indirectly by modifying the local microenvironment. Recent work has shown that AuNPs can disrupt cross talk between cells and alter the mechanical and chemical properties of the extracellular matrix (ECM). This disruption can extend to cellular behaviors such as chemotaxis, the directed migration of cells in response to a chemical gradient. Chemotaxis is responsible for infection and would healing in humans and can be greatly affected by changes in the ECM. Dysfunctions in cellular chemotaxis have been implicated in a variety of health problems such as chronic obstructive pulmonary disease, cystic fibrosis, infertility, and cancer metastasis. , …”
mentioning
confidence: 99%